EFFECT OF STREPTOZOTOCIN AND POLYHERBAL EXTRACT ON BIOCHEMICAL PARAMETERS IN WISTAR RATS - Saniya Begum; J. Selvaraj; V. Ranganathan; N. Babu Prasath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Gymnema sylvestre, Annona muricata and Ocimum sanctum are well known plants available in India and they are commonly used for the treatment of various diseases including diabetes mellitus. A study was conducted to assess the hypoglycemic effect of a polyherbal extract containing these plants (at two different doses of300 and 600 mg/kg bwt) compared with metformin as a standard hypoglycemic drug at a dose of 100 mg/kg bwt in streptozotocin-induced diabetes in rats. As a part of the study, the effect of the polyherbal extract on the renal and hepatic functions was tested in rats. The serum parameters both ALT and AST values in rats were significantly (p < 0.05) higher in diabetic rats treated with polyherbal extract at 300 mg/kg bwt when compared to Groups I, II and III. BUN values were significantly higher in diabetic and metformin treated groups. Creatinine did not differ significantly among different groups. In conclusion, in streptozotocin induced diabetic rats, the polyherbal extract at 300 and 600 mg/kg bwt had no hepatoprotective action. But the same doses had some renal protective function.